PENGARUH EARNING PER SHARE, PRICE TO BOOK VALUE DAN RETURN ON EQUITY TERHADAP HARGA SAHAM - Haerianti Haerianti (Worksheet : Jurnal Akuntansi, 2026)
This study aims to analyze the effect of Earning Per Share (EPS), Price to Book Value (PBV), and Return on Equity (ROE) on stock prices of companies included in the LQ45 Index on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study employs a quantitative method using a multiple linear regression approach. The research population consists of 70 LQ45 companies, with a sample of 19 companies selected through purposive sampling. Data were collected using a documentation method in the form of corporate financial statements. The data analysis techniques include classical assumption tests, t-test, F-test, and the coefficient of determination. The results indicate that partially, EPS and PBV have a positive and significant effect on stock prices, while ROE has a negative effect on stock prices. Simultaneously, EPS, PBV, and ROE have a significant effect on stock prices. The coefficient of determination value of 0.642 indicates that these variables explain 64.2% of the variation in stock prices.